P93 What are the views of overweight and obese adolescents (12–17yrs) attending lifestyle treatment interventions: a qualitative systematic review. (2nd September 2017) - Jones, HM; Al-Khudairy, L; Melendez-Torres, GJ; Oyebode, O
Abstract : Background: A third of all children in England are overweight or obese. Physical and psychosocial effects of obesity in adulthood are now seen in children and adolescents. Current NICE guidance recommends that obese adolescents attend a family-based multi-component weight management service. Cochrane reviews have shown that lifestyle programmes can be effective. However, weight management interventions recruit <2% of the childhood population. For those that do attend weight management interventions, attrition is high. Understanding the views of adolescents is necessary for planning and development of future interventions. The goals of this systematic review include: To explore the views of overweight or obese adolescents aged 12–17 years who have attended a lifestyle treatment intervention. To identify what adolescents deem as successful and unsuccessful components of an intervention to inform future practice, as well as research. Methods: This review examined studies of overweight or obese adolescents who have attended a lifestyle treatment intervention. Interventions were single or multi-component and contained one or more diet, physical activity and behavioural elements. Only studies that collected and analysed data qualitatively were included. There were no language restrictions. Published literature was identified by searching the following databases: MEDLINE, EMBASE, Web of Science, PsycINFO, ASSIA and CINAHL. Reference lists of included studies were screened. Titles and abstracts of identified records were assessed independently by two reviewers. Full texts of all potentially relevant papers were retrieved. Two reviewers assessed each full text and reasons for exclusion were recorded. Differences in opinions were resolved by a third reviewer. Methodological quality was assessed by two reviewers independently as low, medium or high in terms of trustworthiness and reliability of findings. This was done using criteria developed by the EPPI-Centre. Full texts will be opened in NVivo and analysed using thematic synthesis, as described by Thomas and Harden (2008). The certainty of review findings will be assessed using the Confidence in the Evidence from Reviews of Qualitative Research (CERQual) approach. Results: 19 230 records were identified for title and abstract screening. 284 full-texts were screened, with 30 included in the final sample. Conclusion: This review is due for completion in June 2017. Findings will inform development of an adolescent weight management intervention in Coventry, West Midlands. To date, no systematic review has focused on adolescent views of weight management interventions. The views of adolescents should be taken as a starting point when planning future initiatives.